Inclusive Economic Development of Badung Regency: Inter-Time and Inter-Regional Development Analysis - Sarjana, I Made Bram; Saskara, Ida Ayu Nyoman; Mahaendra Yasa, I Nyoman; Yuliarmi, Ni Nyoman (International Ecsis Association, 2024)
The objective of this research is to understand the progress of inclusive economic development in Badung Regency in Bali Province through the analysis of the Inclusive Economic Development Index (IEDI). The research is motivated by two things, first, the issue of inclusivity is an issue amidst the rapid pace of economic development in Badung Regency. Second, the analysis of IEDI data is not yet widely known and used in regional development policy formulation. The method used in this research is descriptive statistics and a literature study. The results of the analysis show that from 2012 to 2021, the average IEDI value for Badung Regency was 5.85 with a decreasing trend. This condition indicates symptoms of widening economic development gaps at a high rate of economic growth. Through this research, it is hoped that analysis of development can be carried out from a comprehensive perspective, later on policy formulation is expected to be oriented towards inclusive economic development.